2010
DOI: 10.1177/1078087409351947
|View full text |Cite
|
Sign up to set email alerts
|

Local News Outlets and Political Participation

Abstract: We investigate how access to local government information affects turnout in municipal elections. We hypothesize that the availability of news focused on local public affairs in an individual's municipality affects her political participation. We anticipate that turnout will be depressed by restricted access to local government news. We test this expectation using survey data from the Los Angeles (California) Designated Market Area (DMA) collected by the Public Policy Institute of California, and the availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
0
24
0
3
Order By: Relevance
“…Positive Kommunikationswirkungen auf die politische Beteiligung finden sich auch auf lokaler Ebene (Filla & Johnson, 2010;Nicodemus, 2004), die Frage nach Unterschieden in den Medienwirkungen zur nationalen Ebene ist aber offen. Hinsichtlich persönlicher Gespräche sollte der positive Einfluss auf die politische Partizipationsbereitschaft bei lokalen Themen größer sein als bei nationalen Themen.…”
Section: Medienwirkungen Auf Partizipationsbereitschaftunclassified
“…Positive Kommunikationswirkungen auf die politische Beteiligung finden sich auch auf lokaler Ebene (Filla & Johnson, 2010;Nicodemus, 2004), die Frage nach Unterschieden in den Medienwirkungen zur nationalen Ebene ist aber offen. Hinsichtlich persönlicher Gespräche sollte der positive Einfluss auf die politische Partizipationsbereitschaft bei lokalen Themen größer sein als bei nationalen Themen.…”
Section: Medienwirkungen Auf Partizipationsbereitschaftunclassified
“…For whites, political efficacy is the only statistically significant variable, in a positive direction. Filla and Johnson's (2010) study on voting frequency in Los Angeles County found that income, gender, political interest, and strength of party identification are statistically significant variables. The coefficients for these variables are all positive, and political interest has the largest impact on voting frequency.…”
Section: Socioeconomic and Psychological Characteristicsmentioning
confidence: 99%
“…Others postulate that race, marital status, home ownership, and other forms of social connectedness are relevant in measuring participation and voting (Filla and Johnson 2010;Krishna 2002;Leighley and Vedlitz 1999;Marschall 2001). Alvarez and Butterfield (1999) analyze voter turnout rates among Latinos and whites and demonstrate that in Los Angeles County, Latinos do not participate as much as whites with other variables controlled.…”
Section: Socioeconomic and Psychological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Filla and Johnson's study of 83 suburban Los Angeles found that voters "who have access to a daily newspaper are more likely to vote than respondents living in communities without newspapers" (686). For Filla and Johnson (2010) "democratic governance is premised upon voter access to information about the problems and opportunities their political community faces, the actions of elected officials, and the policy options available to them" (679).…”
Section: Political Participation: Media and Community Organizationsmentioning
confidence: 99%